Subjetividade, solidariedade e trabalho: a construção dos sentidos do trabalho no contexto da economia solidária - Carvalho, Clarissa de Fátima Nobre (2011)
The contemporary world of work is permeated by a backdrop of profound transformations, exemplified by the change in labor relations, increasingly dynamic and competitive, labor market, which spread into the outsourcing, subcontracting, and modes of organization and production, predominantly centered in the capital. Among the coping strategies of the models of precarious employment and alternative income generation, draws attention to the proliferation of solidarity organizations, which are based on values very different from those most widely used in today\'s society, such as cooperation, mutual aid, democratic decision-making. This specificity motivated this research, which aimed to understand the general meanings attributed to work by members of enterprises based on the principles of Solidarity Economy. The research was conducted from the standpoint of the workers associated themselves and had the theoretical ideas presented by authors such as Antunes (2000), Castel (2005), Singer (2002) and Vygotsky (2001). The methodology for achieving goals followed the referential quality and data collection was conducted through individual interviews. The discursive material collected, in turn, was analyzed based on Content Analysis proposed by Bardin (1977). The data analyzed showed that inserting these projects brings a positive impact on the meanings attributed to work, while remaining references to the notion of working with a formal contract as a guarantee of rights and labor protections.